The impact of ex vivo ozone injection into the synovial fluid in patients with knee osteoarthritis: A controlled clinical trial - Emre Ata; Semiha Özgüç; Mustafa Hüseyin Temel; Hakan Beyaztaş; Selman Aktaş; Eray Metin Güler (Archives of Rheumatology, 2024)
Objectives: This study aimed to examine the effect of varying ozone doses on proinflammatory cytokine levels in the synovial fluid collected from individuals with knee osteoarthritis. Patients and methods: The controlled clinical trial was conducted with 82 patients (61 females, 21 males; mean age: 63.1±10.0 years; range, 40 to 73 years) between 21 April 2023 and 20 May 2023. Synovial fluid samples were collected from the patients under ultrasound guidance and divided into three tubes, one of which was not injected with ozone, and the other two were injected with 10 and 30 gamma (γ) ozone, respectively. The total antioxidant status, total oxidant status, oxidative stress index, interleukin (IL)-1 beta (β), IL-6, and tumor necrosis factor-alpha (TNF-α) in the joint fluids were measured. Results: The oxidative stress index and IL-1 β, IL-6, and TNF-α levels in the synovial fluid were lower at 10 and 30 γ compared to 0 and 10 γ, respectively. In vitro ozone injection at 30 gamma was more effective in reducing proinflammatory cytokines in the synovial fluid than that at 10 and 0 γ. Ozone injection into the pathological joint fluid was more effective in terms of total antioxidant status at 10 and 30 γ compared to 0 and 10 γ, respectively. No significant difference in total oxidant status was observed between the groups. Conclusion: This study showed that in vitro ozone injection at 30 γ was more effective in reducing proinflammatory cytokines in the synovial fluid and in improving total antioxidant status than that at 10 and 0 γ. The results showed the potential significance of the ozone injection dosage in treating knee osteoarthritis.